PEMANFAATAN LAHAN KECIL UNTUK BERCOCOK TANAM SAWI HIJAU DI DESA KOENDRAFO - Ferdinand Tharorogo Wau; Yulianus Buulolo; Herman Giawa; Yuniati Halawa; Enimas Maduwu; Didiana Buulolo; Asnidar Buulolo; Dewima Buulolo; Thomas Polinus Ndruru; Suka Hati Lature (Universitas Nias Raya, 2025)
This study aims to examine the use of small plots of land for growing mustard greens (Brassica rapa var. Parachinensis) in Koendrafo Village. Limited land in rural areas often hinders the community’s demand for fresh vegetables. Using simple cultivation methods utilizing limited yard space, this study observed the growth , yield, and community acceptance of this farming technique. The result indicate that small plots of land can be optimized to produce high- quality mustard greens, provided they are managed using appropriate soil cultivation techniques, organic fertilization, and regular watering. Utilization of these small plots not only contributes to household food security but also opens up economic opportunities for residents throught the sale of the harvest. Thus, the use of small plots of land in Kendafo Village has proven effective and has the potential for sustainable development.